In vitro copper oxide nanoparticle toxicity on intestinal barrier. Issue 2 (27th October 2020) - Bertero, Alessia; Colombo, Graziano; Cortinovis, Cristina; Bassi, Virginia; Moschini, Elisa; Bellitto, Nicholas; Perego, Maria Chiara; Albonico, Marco; Astori, Emanuela; Dalle‐Donne, Isabella; Gedanken, Aharon; Perelshtein, Ilana; et al.
Abstract: The use of CuO nanoparticles (NPs) has increased greatly and their potential effects on human health need to be investigated. Differentiated Caco‐2 cells were treated from the apical (Ap) and the basolateral (Bl) compartment with different concentrations (0, 10, 50 and 100 μg/mL) of commercial or sonochemically synthesized (sono) CuO NPs. Sono NPs were prepared in ethanol (CuOe) or in water (CuOw), obtaining CuO NPs differing in size and shape. The effects on the Caco‐2 cell barrier were assessed via transepithelial electrical resistance (TEER) evaluation just before and after 1, 2 and 24 hours of exposure and through the analysis of cytokine release and biomarkers of oxidative damage to proteins after 24 hours. Sono CuOe and CuOw NPs induced a TEER decrease with a dose‐dependent pattern after Bl exposure. Conversely, TEER values were not affected by the Ap exposure to commercial CuO NPs and, concerning the Bl exposure, only the lowest concentration tested (10 μg/mL) caused a TEER decrease after 24 hours of exposure. An increased release of interleukin‐8 was induced by sono CuO NPs after the Ap exposure to 100 μg/mL and by sono and commercial CuO after the Bl exposure to all the concentrations. No effects of commercial and sono CuO NPs on interleukin‐6 (with the only exception of 100 μg/mL Bl commercial CuO) and tumor necrosis factor‐α release were observed. Ap treatment with commercial and CuOw NPs was able to induce significant alterations on specific biomarkers of protein oxidative damage (protein sulfhydryl group oxidation and protein carbonylation). Abstract : Differentiated Caco‐2 cells were exposed from the apical and basolateral compartment to 0, 10, 50 and 100 μg/mL of sonochemical (synthesized in ethanol or in water) and commercial CuO nanoparticles (NPs), then trans‐epithelial electrical resistance (TEER), cytokine release and biomarkers of protein oxidation were investigated. TEER was affected mostly by the Bl exposure to sonochemical Cu NPs. CuO NPs also induced a significant ( P < .05) release of interleukins 8 and 6, and alterations in biomarkers of protein oxidation.